PENGARUH PENGGUNAAN MEDIA SCRAPBOOK TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA DI SANGGAR BELAJAR KEPONG MALAYSIA - Alia Nurjannah; Dewi Kesuma Nasution (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of using Scrappbook learning media on the critical thinking skills of fourth-grade elementary school students at Sanggar Belajar Kepong Malaysia in the subject of the five senses. This study used a pre- experimental design with a one-group pretest-posttest design. The sampling technique was total sampling, resulting in a sample of six students. Data collection was conducted by administering a critical thinking skills test in the form of an essay. The data analysis technique used was the paired sample t-test. The results showed that the calculated t-value (10.764) > t-table (2.570) and the significance value 0.001 < 0.05, which means that there is an effect of using Scrappbook learning media on the critical thinking skills of fourth-grade elementary school students at Sanggar Belajar Kepong Malaysia. The effect was also demonstrated by the posttest scores being higher than the pretest scores, namely 93,16 > 52.